Germplasm exploration for the genera Capsicum and Phaseolus in south central Bolivia : final report for USDA/UC-Davis/CIF-PAIRUMANI/CIAT/IPGRI supported mission - Debouck, Daniel G. (International Center for Tropical Agriculture, 1994)
A germplasm exploration has been carried out in departments of Cochabamba, Chuquisaca and Tarija in southern Bolivia, for native species of the genera Capsicum and Phaseolus. Germplasm hs been found for the following species: C. annuum (1), C. baccatum (6), C. chaoense (3), C. eximium (2), P. augusti (2), P. lunatus (2), P. vulgaris (27, cultivated forms; 7, wild populations). These findings are discussed in relation to the evolution of these crops and the possibilities of conservation in the area.